Corticofugal Augmentation of the Auditory Brainstem Response With Respect to Cortical Preference - Liu, Xiuping; Zhang, Oliver; Chen, Amber; Hu, Kaili; Ehret, Günter; Yan, Jun (Frontiers in Systems Neuroscience, 2019)
Physiological studies documented highly specific corticofugal modulations making subcortical centers focus processing on sounds that the auditory cortex has experienced to be important. Here, we show the effects of focal conditioning of the primary auditory cortex (FCAI) on auditory brainstem response (ABR) amplitudes and latencies in house mice. FCAI significantly increased ABR peak amplitudes (peaks I – V), decreased thresholds, and shortened peak latencies in responses to the frequency tuned by conditioned cortical neurons. The amounts of peak amplitude increases and latency decreases were specific for each processing level up to the auditory midbrain. The data provide new insights in possible corticofugal modulation of inner hair cell synapses and new corticofugal effects as neuronal enhancement of processing in the superior olivary complex and lateral lemniscus. Thus, our comprehensive ABR approach confirms the role of the auditory cortex as instructor of lower auditory levels and extends this role specifically to the cochlea, superior olivary complex, and lateral lemniscus. The whole pathway from the cochlea to the inferior colliculus appears, in a common mode, instructed in a very similar way.